FACTORY OVERHEAD COST BUDGET - Lismawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Every field of production activity must have a goal to be achieved by the company. Generally the main goal of a company is to get a large profit or profit. Every production activity requires production costs because production costs are aimed at obtaining a higher economic value of the product. Therefore, each company needs raw material costs, direct labor costs and factory overhead costs. Raw material costs, direct labor costs and factory overhead costs are very important because they are one of the techniques for implementing policies on product loading. Is part of the planning process to determine actions for production activities in the future. Provides information to determine actions for production activities.